INADEQUATE LABELING OF ALLERGENIC FOOD: THE RISK FOR INDIVIDUALS WITH FOOD HYPERSENSITIVITY - Camila Cristina Santos de Miranda; Larissa Lovatto Amoriin Gama (Universidade do Estado do Rio de Janeiro, 2018)
Objective: To analyze labeling adequacy of allergenic foods in accordance with Resolution no. 26, of July 2, 2015. Methodology: The agreement of allergen declarations was evaluated on 221 labels of processed foods commercialized in three distinct supermarket chains. The products were subdivided into ten food groups (breads and cereals; fish and crustaceans; eggs and derivatives; oily seeds; milk and derivatives; soybeans and derivatives; pastas; sweets, cakes and biscuits; meats and processed meats and alcoholic beverages) and were categorized as "inadequate" when they failed to meet any criteria set forth in the resolution. In order to detail the inadequacies, the following classifications were adopted: incorrect location of the declaration on the label, incomplete declaration and/or inadequate formatting and nonexistent declaration. Results: The evaluated food labels showed that 31.7% (n=70) were identified as inadequate. Of these inadequacies, it was observed that 48.6% were classified as "Nonexistent Declaration". It was also observed that the inadequacies were found in the ten food groups. Conclusion: National regulatory labeling norms have innovated regarding the protection of allergic consumers, however, there are still several irregularities in their compliance. Investigations of this nature are relevant to public health and must be carried out to demand supervision and implementation of the current legislation. DOI: 10.12957/demetra.2018.32906